Analysis of applied ash transport systems from flue gas dust collectors in power and heating boilers with grate furnaces - Janik , Kazimierz; Janik , Ireneusz; Janik , Adrianna; Rataj, Zbigniew (Instal, 2019)
This paper analyzes the conveyors used in dust collection and transport systems from grate boilers in industrial and heating energy. Attention was paid to the construction of the most commonly used types of dust conveyors, their construction and operational parameters. A comparative assessment was made of electricity consumption for the drive of the equipment. The analysis helps in making technical and financial decisions.
Keywords: Dust collector; electrostatic precipitator; dust collection and transport system; belt conveyor; screw conveyor; link-belt conveyor; rope conveyor; chain conveyor; spiral conveyor; plate; chain; trough charge; bath charge; conveyor capacity; length; diameter; power; life time; cost; price